A Regional Geography Approach to Understanding the Atmospheric Changes as a Consequence of the COVID-19. Lockdown in highly populated Spanish cities. - Rodrigo-Comino, Jesús; Senciales-González, José María (MDPI, 2021)
Spain has been highly impacted by the COVID-19 pandemic, which is reflected at different scales. From an economic point of view, lockdowns and the reduction of activities have damaged the country (e.g., complete lockdown from March 13 to June 21, 2020). However, it is not clear if the associated environmental impacts could be observed in 2020. Currently, studies on the effects of the lockdown (e.g., decrease in economic activities, transport and social communication) on specific parameters related to climate change, such as air temperature or air pollution, due to a drastic decrease in human activities are rare. They are focused on specific cities and short periods of time. Therefore, the main goal of our research will be to assess the records of air temperature and air quality during the whole of 2020 compared to references from previous years (30 years for air temperature and 10 for air quality). We paid attention to the possible effects of the reduction of activities (e.g., tourism and transport) in March, April and May and the different restrictions of each lockdown in Spain. To achieve this goal, five urban climate stations with long-term time series within the most populated cities of Spain were analyzed (Barcelona, Madrid, Málaga, Sevilla and Valencia). We conclude that it is possible to affirm that the impacts of the COVID-19 pandemic on the atmospheric conditions in 2020 are not clear and not strictly focused on the lockdown or reduction of activities in these urban areas. No evidence of a reduction in the annual air temperature was found, and only a minimum reduction of rates of pollutants was registered in the highly populated cities of Spain. Therefore, it is worth confirming that these changes could be affected by other factors, but on a global scale and not directly due to the COVID-19 pandemic.Considering recent studies on the relationships between air pollutants, temperature and the spreadability of COVID-19, green policies must be further imposed...
Keywords: Pandemia de la Covid-19, 2020 - Aspectos sociales; Cambios climáticos; Geografía urbana; COVID-19; Epidemiology; Data mining; Climate variations; Regional geography